Detection of components on power lines using images captured by UAVs - Castro, Pedro Arfux Pereira Cavalcante de; Gonçalves, Wesley Nunes; Marcato Junior, José (Anais do Workshop de Visão Computacional (WVC), 2023)
Preventive maintenance of power poles, including component inspection, is essential to ensure the continuous supply of electricity to cities. Despite its importance, the current practice of visually identifying issues demands considerable time and effort. To address this challenge, this study proposes the use of automatic methods for power pole inspection, aiming to reduce inspection time and predict potential component replacements. The investigation leverages convolutional neural networks based on Faster R-CNN to automatically evaluate power pole conditions. A dataset was generated from 848 images obtained from a repository available on the internet. The resulting neural network from the training process has an average precision of 98.7% with an Intersection over Union (IoU) of 50% and 98.2% with an IoU of 75% for high-voltage electrical network components.